Operational Efficiency and Financial Structure as Determinants of Return on Assets: Panel ARDL Estimation in the Banking Industry - Andri Helmi Munawar; Ageng Asmara Sani; Dede Arif Rahmani; Cindera Syaiful Nugraha; Mira Rahmawati; Sakifah Sakifah (Jurnal Manajemen Bisnis, 2026)
This study examines the effects of operational efficiency and financial structure on the profitability of conventional commercial banks in Indonesia during 2014–2022. Profitability is measured by Return on Assets (ROA), while the explanatory variables include Operating Expenses to Operating Income (BOPO), Debt to Asset Ratio (DAR), Capital Ratio (CR), and bank size (SIZE). Using secondary data from the annual financial statements of 12 conventional commercial banks, this study applies the Panel Autoregressive Distributed Lag (Panel ARDL) model with the Pooled Mean Group (PMG) estimator to distinguish short-run dynamics from long-run equilibrium relationships. The findings confirm the existence of a stable long-run relationship among the variables, as indicated by a significant error correction term. In the long run, DAR has a significant negative effect on ROA, while CR has a significant positive effect. SIZE shows a significant negative relationship with ROA, suggesting that larger banks in the sample may face scale-related inefficiencies. BOPO also has a positive and significant long-run effect on ROA, indicating that operating expenses may reflect broader operational and revenue-related conditions rather than cost inefficiency alone. In the short run, only CR and SIZE significantly affect ROA, whereas DAR and BOPO do not show significant effects. These findings highlight that bank profitability is shaped by dynamic internal adjustment processes and provide implications for bank managers and regulators in maintaining prudent leverage, strengthening capital resilience, and improving the quality of operational management.